2014
DOI: 10.3233/bme-141076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the robo-horse and real horse movements for hippotherapy

Abstract: While the novel robotic hippotherapy system has gradually gained clinical application for therapeutic intervention on postural and locomotor control in individuals with neurological or musculoskeletal impairments, the system's validity and reliability for the robotic hippotherapy system has not been well established. The objective of the current study was to investigate the validity and test-retest reliability of the robotic hippotherapy system by comparing with real horse movements. The 3-axis accelerometer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
(22 reference statements)
2
10
0
1
Order By: Relevance
“…The similarity between HR and HRS was confirmed by expert riders with more than five years experience with previous research involving HR and HRS similarity (Park et al, 2014). This previous research showed a high HR/HRS correlation (R 2 ¼ 0.997) in time-to-peak acceleration for evaluating movement patterns and obtaining accurate information about spatiotemporal parameters (Park et al, 2014). Figures 1 and 2 show HR and HRS arrangements.…”
Section: Methodssupporting
confidence: 63%
See 3 more Smart Citations
“…The similarity between HR and HRS was confirmed by expert riders with more than five years experience with previous research involving HR and HRS similarity (Park et al, 2014). This previous research showed a high HR/HRS correlation (R 2 ¼ 0.997) in time-to-peak acceleration for evaluating movement patterns and obtaining accurate information about spatiotemporal parameters (Park et al, 2014). Figures 1 and 2 show HR and HRS arrangements.…”
Section: Methodssupporting
confidence: 63%
“…Core muscle activation was evaluated for three gait speeds selected by three experts (two professors from the School of Equine Science, Department of Physical Therapy, and one research professor in motor control and development): (a) walk ¼ 80 m/minute, (b) slow trot ¼ 135 m/minute, and (c) fast trot ¼ 159 m/minute. The similarity between HR and HRS was confirmed by expert riders with more than five years experience with previous research involving HR and HRS similarity (Park et al, 2014). This previous research showed a high HR/HRS correlation (R 2 ¼ 0.997) in time-to-peak acceleration for evaluating movement patterns and obtaining accurate information about spatiotemporal parameters (Park et al, 2014).…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…8 Even though horseback-riding simulators have successfully been used as a substitute for real horses, recent research studies have highlighted significant differences in motion between a real horse and simulators. [9][10][11] Walker et al measured the displacement at the saddle and found that a simulator had smaller movements than a real horse in specific directions. 9 This difference may not be a problem if the simulator is just used for entertainment or fitness.…”
Section: Introductionmentioning
confidence: 99%